Analisis Pendapatan Petani Kopi Gondowido Ngebel Ponorogo - Takim Mulyanto; Rahmad Kurniawan; Edy Prayitno; Muhammad Syaikhi Abdul Rahman Wahid (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This study aims to determine the income level and feasibility of coffee farming in Gondowido village, Ngebel district, Ponorogo country, by analyzing total cost and total income. Coffee cultivation in Gondowido is expected to increase, fully exploiting the potential and human resources of the region. With the help of computer analysis, we can get an overview of the sales prices and profits that affect the income of coffee farms. A survey method was used to collect primary and secondary data. Secondary data includes the conditions under which people grow coffee. Primary data was obtained through a survey method to determine data collection of factors affecting coffee production. The data collection method was filling out questionnaires from 31 specially selected coffee growers. RC Ratio and BEP are used in feasibility analysis methods. The results showed an R/C ratio of 2.05, indicating that the effort was feasible but needed improvement for optimal results. The value of the cost-benefit analysis of 24.9 kg is IDR1,119,159.21.